Establishment of fishing cat cell biobanking for sustainable conservation - Sukparangsi, Woranop; Thongphakdee, Ampika; Karoon, Santhita; Suban Na Ayuthaya, Nattakorn; Hengkhunthod, Intira; Prakongkaew, Ratchapon; Bootsri, Rungnapa; Sikaeo, Wiewaree (Frontiers in Veterinary Science, 2022)
The fishing cat (Prionailurus viverrinus) is a vulnerable wild felid that is currently under threat from habitat destruction and other human activities. The zoo provides insurance to ensure the survival of the fishing cat population. Creating a biobank of fishing cats is a critical component of recent zoo strategies for securely stocking cell samples for long-term survival. Here, our goal was to compare cell biobanking techniques (tissue collection, primary culture, and reprogramming) and tissue sources (ear skin, abdominal skin, testis) from captive (n=6)/natural (n=6) versus living (n=8)/postmortem (n=4) fishing cats. First, we show that dermal fibroblasts from the medial border of the helix of the ear pinna and abdominal tissues of living fishing cats can be obtained, whereas postmortem animals provided far fewer fibroblasts from the ears than from the testes. Furthermore, we can extract putative adult spermatogonial stem cells from the postmortem fishing cat's testes. The main barrier to expanding adult fibroblasts was early senescence, which can be overcome by over-expressing reprogramming factors through felid-specific transfection programs, though we demonstrated that reaching iPSC state from adult fibroblasts of fishing cats was ineffective with current virus-free mammal-based induction approaches. Taken together, the success of isolating and expanding primary cells is dependent on a number of factors, including tissue sources, tissue handling as well as nature of limited replicative lifespan of the adult fibroblasts. This study provides recommendations for tissue collection and culture procedures for zoological research to facilitate the preservation of cells from both postmortem and living felids.